2021
DOI: 10.3390/magnetism1010004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Flow and Curing Behavior of Hard Magnetic Fillers in Thermosets and the Magnetic Properties

Abstract: Polymer bonded magnets based on thermoplastics are economically produced by the injection molding process for applications in sensor and drive technology. Especially the lack of orientation in the edge layer, as well as the chemical resistance and the creep behavior limit the possible implementations of thermoplastic based polymer bonded magnets. However, thermoset based polymer bonded magnets have the opportunity to expand the applications by complying with the demands of the chemical industry or pump systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Several factors were detected to affect the flow and curing behaviour of polymer-bonded magnets based on an epoxy resin (EP), whereby those factors can be applied to any filler system with a high filler amount in a thermoset compound due to the fact that they are based on the material behaviour of particles. Within this paper, it was shown that SrFeO acts like an adhesive filler in a network, being integrated, whereas NdFeB displays a network with a non-adhesive force, creating a hole in the network [30]. This theory of the filler behaviour in the network based on [29] is assumed to influence the viscosity of the compound systems, and with that a correlation to the magnetic and mechanical properties is likely.…”
Section: Flow Behaviour and Reaction Kinetics Of Thermosetsmentioning
confidence: 91%
See 2 more Smart Citations
“…Several factors were detected to affect the flow and curing behaviour of polymer-bonded magnets based on an epoxy resin (EP), whereby those factors can be applied to any filler system with a high filler amount in a thermoset compound due to the fact that they are based on the material behaviour of particles. Within this paper, it was shown that SrFeO acts like an adhesive filler in a network, being integrated, whereas NdFeB displays a network with a non-adhesive force, creating a hole in the network [30]. This theory of the filler behaviour in the network based on [29] is assumed to influence the viscosity of the compound systems, and with that a correlation to the magnetic and mechanical properties is likely.…”
Section: Flow Behaviour and Reaction Kinetics Of Thermosetsmentioning
confidence: 91%
“…This is portrayed in Figure 1B [29]. In [30], the influence of hard magnetic particles on the flow and curing behaviour of highly filled thermoset-based compounds was investigated. Several factors were detected to affect the flow and curing behaviour of polymer-bonded magnets based on an epoxy resin (EP), whereby those factors can be applied to any filler system with a high filler amount in a thermoset compound due to the fact that they are based on the material behaviour of particles.…”
Section: Flow Behaviour and Reaction Kinetics Of Thermosetsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] proved that a pure iron phase within the filler NdFeMo-N supports the growth of magnetic domains in EP-based systems by nucleation [20]. The first methodical attempts to generate a basic and fundamental understanding of thermoset-based polymer bonded magnets, fabricated in the injection moulding process, were made in [21,22], where a material model in terms of the cross-link structures between the filler and the matrix material was found. Further, the influence of this model, or more precisely the influence of the material properties on the magnetic and mechanical properties, was characterized.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…These devices contain different groups of magnetic materials, which are expected to have the best possible properties with minimum investment [1][2][3]. That is why researchers all over the globe are trying to meet the need by creating new alloy compositions or different composites and even their preparation can have a significant influence on their final magnetic properties [4,5].…”
Section: Introductionmentioning
confidence: 99%